Tinjauan Hukum Islam Terhadap Upah Pembajak Sawah di Desa Klesem Pacitan - Muzakki, Harir; Sumanto, Ahmad (al-'adalah, 2017)
This paper discusses the review of Islamic law regarding the contract of renting a tractor to plow the fields in Klesem Village, Kebon Agung Subdistrict, Pacitan Regency. The aim is to find out whether the practice is in accordance with Islamic law or not. In general, the wage contract in Klesem Village can be classified into the ijarah contract in Islamic law. The main principle in the ijarah contract is mutual benefit and prohibited from judging. Determination of wages must be clear which includes the amount of wages and the procedure for payment. This study finds out that, plow machine service providers often do not keep the time and ask for additional from the wages previously promised. Determination of wage changes and cancellation or termination of contracts unilaterally is certainly detrimental to the farmers. Thus, although in general the practice of renting tractors in the village of Klesem is legal according to Islamic law, there are still practices violating the principles of Islamic law.